Perancangan Permukiman Dengan Pendekatan Arsitektur Neo-Vernakuler (Studi Kasus Kampung Kara'ba) - Eko Saputra; Meldawati Artayani; Noviar Nurdin Kasim (Universitas Muslim Indonesia, 2021)
Kara'ba Kampong is a fisherman's kampong in the cost city of Makassar which is unattended and less organized. Besides that, there is no legality settled. Kara'ba Kampoong is included in the prone to natural disasters category such as tidal waves, floods, whirlwinds, and also threats of evictions that make people restless, and even the surrounding development forced the fishing community in Kara'ba to change their job. It also causes the arrangement discourse and planning of Kara'ba Kampong. So, it is very important the existence of extracting fisherman kampong, so that later can be included in the design plan. By using the participative method or involving the community and related parties overall and field observation. This writing aims to know about existing conditions and activities in Kara'ba Fisherman Kampong. In the cost city of Makassar, many kinds of existing conditions allow being included in designing planning of Kara'ba Fisherman Kampoong, but some of them should not exist for the creation of a joint design, which is expected to solve the problems in the future, so by that process designing of Kara'ba settlement can be created which is the character of the Fisherman Kampong Bugis- Makassar with infrastructure, public facilities, social, adequate economy, and four types of dwellings are the transformation of traditional house renewal Bugis-Makassar with architecture neo-vernacular